The Value of Eccentric Infrared Photorefraction in Evaluating Keratoconus. Issue 10 (6th October 2022) - Patel, Avina M.; Kumar, Preetam; Vaddavalli, Pravin K.; Bharadwaj, Shrikant R.
Abstract : SIGNIFICANCE: Nonlinearity in the luminance profile of eccentric, infrared photorefraction may be used to differentiate corneal diseases such as keratoconus that distort the cornea, relative to regular refractive errors. PURPOSE: This study aimed to determine the profile of eccentric, infrared photorefraction in keratoconus as a prototypical disease model for distorted corneas and identify a parameter in this profile for differentiating such disease conditions from healthy controls. METHODS: Photorefraction reflex of 75 eyes with forme fruste to advanced keratoconic cases and that of 75 eyes of controls with regular refractive errors (spherical equivalent, +0.50 to −11.75 D; astigmatism, −0.50 to −4.50 D across 0 to 180° axes) were obtained over their natural pupils under unaided viewing using a custom-designed photorefractor placed at 1 m from the subject. The test was repeated in 10 controls with 4 and 6 D of trial-lens–induced myopia and myopic astigmatism at 0, 90, 45, and 135°. Linear regression was performed on the luminance profile across the pupil, and the departure of the data from linearity was estimated using the average residual error of the fit (Resavg ). RESULTS: Photorefraction profiles varied linearly across the pupil in controls, with slopes increasing with refractive error ( r = 0.87; P < .001) and Resavg remaining invariant of refractive error ( r = −0.29; P > .4). Corresponding profiles in keratoconus significantly departed from linearity, with Resavg progressively increasing with disease severity ( r = 0.66; P < .001). Resavg of 0.03 gray-scale units/pixel distinguished keratoconus from controls with sensitivity increasing from 66.7 to 100% for mild to advanced keratoconus and specificity remaining ≥97.1% across disease severity. Induced myopia and myopic astigmatism produced predictable changes in luminance profile slopes but with no change in Resavg values. CONCLUSIONS: Unlike regular myopia and astigmatism, the photorefraction reflex is significantly nonlinear in keratoconus because of the distorted cornea. Measures of nonlinearity in luminance profile may be incorporated in commercial photorefractors for differentiating such disease conditions from regular refractive errors.